Analisis Hukum Proses Pergantian Antar Waktu (PAW) Anggota DPRD Kabupaten Empat Lawang Terkait Pelanggaran AD/ART Partai Politik - Reza, Mehmed; Salia, Erli; Saptawan, Ardiyan; Mahfuz, Abdul Latif (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of this paper is that Time Between Time Switching (PAW) is a mechanism in the representative system to replace board members who resign, die, or are dismissed. This research focuses on legal analysis of the PAW process of members of the Four Lawang Regency DPRD who are involved in violations of the Articles of Association / Bylaws (AD / ART) of political parties. The method used is normative legal research with a statutory and case approach. The results showed that the PAW process due to violations of political parties' AD/ART refers to applicable regulations but often causes controversy. This is due to the vagueness of the definition of "violation" in AD/ART and how it is enforced. In addition, the internal political dynamics of parties and the interests of various parties often influence the PAW process, which is supposed to be neutral and objective. In conclusion, there needs to be further revision and clarification regarding the definition of violations in AD/ART as well as a firmer and more transparent law enforcement mechanism to ensure the integrity and accountability of members of the Four Lawang Regency DPRD.